2008
DOI: 10.3354/ab00084
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific seasonal variation in the carotenoid content of sea urchin gonads

Abstract: This study documents the effect of sex on gonad carotenoid content during the annual reproductive cycle of Strongylocentrotus droebachiensis from northern Norway. Male and female S. droebachiensis exhibited distinctly different patterns of carotenoid variation, with seasonal carotenoid depletion and replenishment in females and carotenoid retention in males. Females lost approximately 71.1% of their echinenone during spawning, and compensated for the loss by active deposition during gonad regrowth. Female caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The assimilation of carotenoids in the gonads suggests that they play an important role in sea urchin reproduction. In support of this hypothesis, it has been observed that gonad carotenoid concentrations fluctuate in accordance with the annual reproductive cycle [9], [19]. Furthermore, it has been demonstrated that carotenoids are incorporated into oocytes and may provide anti-oxidant protection to spawned eggs and juveniles during early development [20], [21], [22].…”
Section: Introductionmentioning
confidence: 78%
“…The assimilation of carotenoids in the gonads suggests that they play an important role in sea urchin reproduction. In support of this hypothesis, it has been observed that gonad carotenoid concentrations fluctuate in accordance with the annual reproductive cycle [9], [19]. Furthermore, it has been demonstrated that carotenoids are incorporated into oocytes and may provide anti-oxidant protection to spawned eggs and juveniles during early development [20], [21], [22].…”
Section: Introductionmentioning
confidence: 78%
“…Protein, lipids, carotenoids and other nutrients build up in the gonads prior to spawning (Borisovets et al, 2002;Griffiths & Perrott, 1976;Hagen et al, 2008;Tsushima & Matsuno, 1990). Protein, lipids, carotenoids and other nutrients build up in the gonads prior to spawning (Borisovets et al, 2002;Griffiths & Perrott, 1976;Hagen et al, 2008;Tsushima & Matsuno, 1990).…”
Section: Erythrogramma the Dominant Presence Of Echinenone Is Consismentioning
confidence: 99%
“…Male sea urchins may not require annual carotenoid replenishment because sperm does not contain carotenoids and overall carotenoid content in male gonads tends to be seasonally stable. When males reach a saturation threshold for echinenone either the uptake or bioconversion of β,β-carotene is curtailed (Hagen et al, 2008). High-quality sea urchin gonads have a uniform yellowish-orange color which is a reflection of its carotenoid content, and substandard color is a direct result of carotenoid levels being either too low, leading to paleness or too high, leading to dark miscoloration (i.e., dark red/brown).…”
Section: Carotenoid Pigments In the Plant-animal Interfacementioning
confidence: 99%
“…The gonadas of sea urchins exhibit a pattern of seasonal carotenoid depletion and replenishment in females and carotenoid retention in males (Hagen et al, 2008). Echinenone is preferentially incorporated into the eggs and therefore female urchins need to replenish their echinenone content on an annual/seasonal basis.…”
Section: Carotenoid Pigments In the Plant-animal Interfacementioning
confidence: 99%
See 1 more Smart Citation